Object-oriented analysis and design : - O'Docherty, Mike (John Wiley and Sons, 2005)
The book is programming language agnostic - so code is kept to a minimum to avoid detail and deviation into implementation minutiae. A single case study running through the text provides a realistic example showing development from an initial proposal through to a finished system. Key artifacts such as the requirements document and detailed designs are included. For each aspect of the case study, there is an exercise for the reader to_produce similar documents for a different system